Lytic Polysaccharide Monooxygenases - Muraleedharan, Madhu Nair; Rova, Ulrika; Christakopoulos, Paul (Extremophilic Enzymatic Processing of Lignocellulosic Feedstocks to Bioenergy, 2017)
Lytic Polysaccharide Monooxygensaes have now been evolved as one of the most promising enzymes, attracting huge research attention due to their potential use in saccharification of lignocellulosic biomass for the production of fuels and value added chemicals. In the presence of molecular oxygen, these copper depended enzymes break the recalcitrant cellulose chain by a combined oxidative and hydrolytic action, and increase the substrate accessibility for other cellulases to work. This ‘boosting effect’ and ability to act in synergy makes them important subject to research, towards the future goal of sustainable bioeconomy. Diversity of this enzyme group ranges from early discovered chitin and cellulose active ones, to the recently identified hemicellulose and starch active ones. In this chapter we present a brief summary about LPMOs and the findings related to them from their discovery to the recent developments.